2020
DOI: 10.1002/jbio.201960144
|View full text |Cite
|
Sign up to set email alerts
|

Determination of causes of death via spectrochemical analysis of forensic autopsies‐based pulmonary edema fluid samples with deep learning algorithm

Abstract: This study investigated whether infrared spectroscopy combined with a deep learning algorithm could be a useful tool for determining causes of death by analyzing pulmonary edema fluid from forensic autopsies. A newly designed convolutional neural network-based deep learning framework, named DeepIR and eight popular machine learning algorithms, were used to construct classifiers. The prediction performances of these classifiers demonstrated that DeepIR outperformed the machine learning algorithms in establishin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Yue et al [47] compared the multilayer perceptron (MLP), long short-term memory network and CNN deep learning models regarding the diagnosis of abnormal thyroid function, and the results revealed that the CNN performed best with an accuracy rate of 96.5%. Lin et al [48] proved that a CNN-based deep learning framework outperformed other machine learning algorithms in establishing classifiers to determine causes of death by analyzing pulmonary edema fluid from forensic autopsies. However, according to investigation, most of the application studies based on CNN deep learning models focused on 1D vibrational spectroscopy [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Yue et al [47] compared the multilayer perceptron (MLP), long short-term memory network and CNN deep learning models regarding the diagnosis of abnormal thyroid function, and the results revealed that the CNN performed best with an accuracy rate of 96.5%. Lin et al [48] proved that a CNN-based deep learning framework outperformed other machine learning algorithms in establishing classifiers to determine causes of death by analyzing pulmonary edema fluid from forensic autopsies. However, according to investigation, most of the application studies based on CNN deep learning models focused on 1D vibrational spectroscopy [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Given a dataset of N centered observations in a d-dimensional space PCA diagonalizes the covariance matrix where C is a covariance matrix, To solve the Eq. ( 5) using eigen values ( 1) Lin et al [82] investigated the diagnosis and progression of illnesses to integrate bio-fluid-based infrared spectroscopy into the clinical area. The authors looked at using Fourier transform infrared micro spectroscopy to detect abrupt cardiac death.…”
Section: Role Of Ai To Predict Pulmonary Edema Pulmonary Embolism Cov...mentioning
confidence: 99%
“…Lin et al [ 82 ] investigated the diagnosis and progression of illnesses to integrate bio-fluid-based infrared spectroscopy into the clinical area. The authors looked at using Fourier transform infrared micro spectroscopy to detect abrupt cardiac death.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting classifier is then used to assign class labels to test instances for which predictor feature values are known but class label values are unknown. Accordingly, in forensic medicine field, machine-learning algorithms have also been applied to determine the cause of death, infer skeletal age, and estimate the postmortem interval with vitreous humour, drowning fluid, limb long bone, and other biological specimens [ 16–21 ]. Despite numerous advances in methodology in the past years, forensic medicine research scientists continue to rely heavily on parametric models (e.g.…”
Section: Introductionmentioning
confidence: 99%